DAMAGE OF SUNN PEST Eurygaster integriceps Put. ON INFESTED LEAVES, NON BEARING SPIKE TILLERS AND HARVEST INDEX FOR FOUR WHEAT VARIETIES IN DOHUK PROVINCE - Suaad I. Abdullah (Mesopotamia Journal of Agriculture)
The field study, to estimate the damage of the nymphs and adults of Sunn Pest Eurygaster integriceps Put. for four wheat varieties (Aras,Tamuz-2, Atra,S and Crezo) in Dohuk province, during both seasons 2004-2005 and 2005-2006, showed that an increase in the adult Sunn Pest from one pair to five pairs/m2 and from five nymph to ten nymphs/m2, cause increasing in the levels of number of infested leaves/m2, percentage of non bearing spike tillers/m2, whereas it decreased harvest index (%) for wheat varieties Aras, Tamuz-2, Atra,S and Crezo. The above studied characteristics have influenced greatly in the case of bread wheat in comparison with to the durum wheat. The late ripened bread wheat variety (Tamuz-2) has been influenced more than the others as compared to the early ripened durum wheat variety (Atra,S) which had been influenced less, especially when added adult Sunn Pest with an average of (15.33 & 116.00) , (9.67 & 87.33) and (14.00 & 131.33) , (14.00 & 94.00) infested leaves/m2, when added one pair of adults to five pairs /m2 for two varieties, (Tamuz-2) and (Atra,S), in the first and second season, respectively. And (5.93 & 35.80) , (5.03 & 18.77) and (4.77 & 34.07) , (3.50 & 15.27) percentage of non bearing spike tillers/m2, when added one pair of adults to five pairs /m2 for two varieties, (Tamuz-2) and (Atra,S), in the first and second season, respectively. And (36.37 & 31.40) , (27.37 & 24.63) and (37.47 & 32.53) , (28.20 & 25.17) harvest index (%) for two wheat varieties (Tamuz-2) and (Atra,S), in the first and second season, respectively.